2006
DOI: 10.4102/sajhrm.v4i3.101
|View full text |Cite
|
Sign up to set email alerts
|

Human Resources Practitioners’ Perceptions Of Their Role And Responsibility In Managing HIV/Aids In Industry

Abstract: The central question to be examined revolved around an analysis of the perceptions of Human Resources Practitioners regarding their role and responsibility in the management of HIV/AIDS in industry. A convenience sample of HR Practitioners was used in a cross-sectional design. A questionnaire measuring the constructs of managing HIV/AIDS in industry, as well as a biographical questionnaire was administered. The questionnaire proved to be reliable. A Cronbach alpha coefficient of 0,82 and 0,71 was obtained. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…These results partially confirm the original three-factor model of Schutte (2015), but add the factor Business acumen, resulting in a four-factor solution for the Business intelligence dimension. The results are also in line with the findings of Van Wyk (2006) and Schultz (2010), who found that business knowledge is an important HR professional competency in the South African context.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results partially confirm the original three-factor model of Schutte (2015), but add the factor Business acumen, resulting in a four-factor solution for the Business intelligence dimension. The results are also in line with the findings of Van Wyk (2006) and Schultz (2010), who found that business knowledge is an important HR professional competency in the South African context.…”
Section: Discussionsupporting
confidence: 91%
“…Empirical research on competency requirements for HR professionals in the South African context is scant. The few detailed empirical studies that were conducted in this field focused primarily on the desired roles and practices of HR practitioners in South African organisations (Coetzee, Mitonga-Monga & Swart, 2014;Magau & Roodt, 2010;Scheepers & Schuping, 2011;Schultz, 2010;Steyn, 2008;Van der Westhuizen, Van Vuuren & Visser, 2003;Van Vuuren & Eiselen, 2006;Van Wyk, 2006). Furthermore, the results of these studies illustrate the confusion regarding the roles and responsibilities of HR practitioners and their lack of competence to fulfil key roles.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, HR practitioners are limited in applying innovation, talent management, HR metrics, and HR business knowledge. These results concur with those of previous studies which found that HR professionals are still not allowed to play a strategic role in South African organisations and, as a result, HR competencies and practices are poorly applied (see Barkhuizen, 2015;Schultz, 2010;van Wyk, 2006;Walters, 2006). These findings are concerning, given that the respondents ranked all the measured HR competencies as important.…”
Section: Discussionsupporting
confidence: 82%
“…Schultz (2010) found that the HR department in a merged South African higher education institution displayed poor personal skills, HR business knowledge, and management skills. A study by van Wyk (2006) highlighted the lack of sufficient business knowledge among HR practitioners regarding a social responsibility issue such as HIV and AIDS. The HR practitioners, however, did acknowledge the importance of educating employees on social responsibility issues.…”
Section: Literature Review Human Research Management Role and Competementioning
confidence: 99%